Perfection of methods of support of enterprise is in Republic of Kazakhstan (Вестник КазНУ. Серия Экономическая, 2016)
In this article the modern ways of perfection of government control offer on development of enterprise. Creation of attractive environment is needed. In this connection, needed exposure of effective and stimulant methods of state support for development of enterprise.